Effect of Alumina NANOPARTICLES as Additive on the Friction and Wear Behavior of POLANGA based Lubricant - Singh, Yashvir; Sharma, Abhishek; Singh, Nishant; Singla, Amneesh; P. Dwivedi, S.; Kumar Srivastava, Ashish (International Journal of Engineering and Technology, 2018)
Environment degradation and non-biodegradability are the major problems associated with mineral-oil based lubricants. Non-edible vegetable oils are one of the suitable substitutes for the mineral oils. In this study, polanga oil was used as the lubricant to check its feasibility for the tribological behaviour. Alumina nanoparticles are added to the polanga oil on a weight-percentage basis. The variation of alumina (Al2O3) nanoparticles concentration with polanga oil was evaluated for the coefficient of friction and wear analysis.Â Minimum coefficient of friction and wear was observed at 0.075% % concentration which gets further increased at 0.1 % concentration. The smooth surface of the pin was observed at 0.075 % nanoparticles concentration with the comparison to base polanga oil. Maximum total acid number changes was obtained at 0.1% concentration.Â Â